2021
DOI: 10.1515/zwf-2021-0153
|View full text |Cite
|
Sign up to set email alerts
|

Sensornetzwerke zur Kugellagerdiagnose am rotierenden Innenring

Abstract: Kugellager sind Verbindungsglieder zwischen stillstehenden und bewegten Komponenten. Insbesondere im Bereich der Werkzeugmaschinen sind Kugellager hohen Belastungen ausgesetzt und sorgen bei einem Defekt zu hohen Ausfallkosten. Um diese Defekte schneller zu erkennen, kommt eine ultraschallbasierte Diagnosetechnologie am Kugellagerinnenring zum Einsatz. Der Applikationsort der Technologie setzt eine energetische Versorgung voraus, die keine begrenzte Lebensdauer besitzt. Mithilfe eines elektromagnetischen Energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In this context, few solutions have realized an autonomous solution-based energy harvesting and wireless sensor node for IIoT devices in industry and predictive maintenance. In [20][21][22], a sensor network powered through an electromagnetic harvester was developed for the diagnosis of ball bearings; nevertheless, the results showed that the system required 100 mW to measure and transmit the information, which was quite high. Further, in [22], a wireless sensor node was developed for structural health monitoring and had the advantage of low power consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, few solutions have realized an autonomous solution-based energy harvesting and wireless sensor node for IIoT devices in industry and predictive maintenance. In [20][21][22], a sensor network powered through an electromagnetic harvester was developed for the diagnosis of ball bearings; nevertheless, the results showed that the system required 100 mW to measure and transmit the information, which was quite high. Further, in [22], a wireless sensor node was developed for structural health monitoring and had the advantage of low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In [20][21][22], a sensor network powered through an electromagnetic harvester was developed for the diagnosis of ball bearings; nevertheless, the results showed that the system required 100 mW to measure and transmit the information, which was quite high. Further, in [22], a wireless sensor node was developed for structural health monitoring and had the advantage of low power consumption. Nevertheless, the solution had a limitation in terms of the photovoltaic source, which led to a long charging time of 30 min.…”
Section: Introductionmentioning
confidence: 99%